Profesionalisme Reflektif Situasional Guru Vokasi Pada Kelas Heterogen: Studi Etnografi Sekolah Pariwisata - I Gusti Kadek Surya Adnyana; I Wayan Santyasa; I Made Tegeh (Cetta: Jurnal Ilmu Pendidikan, 2026)
Research on vocational teachers’ professional competence has generally positioned professionalism as pedagogical ability and mastery of subject matter that are administrative and normative in nature, while the reflective and situational dimensions of teaching in heterogeneous classrooms remain underexplored, particularly from the perspective of educational ethnography. This study aims to analyze teachers’ professional practices in actualizing vocational learning competencies within heterogeneous classrooms at SMKS Pariwisata Triatma Jaya Singaraja. The study employed a qualitative approach using an educational ethnography design. Data were collected through participant observation, in-depth interviews, and documentation involving five vocational teachers, the principal, and thirty students. Data analysis was conducted interactively through data condensation, data display, verification, and conclusion drawing, which were further deepened through domain, taxonomic, componential, and cultural theme analyses. The findings reveal that teachers’ professional competence develops adaptively through teaching experience, pedagogical improvisation, and situational reflection in responding to the dynamics of heterogeneous classrooms. However, the learning process remains dominated by teacher-centered approaches, the integration of theory and practice is still sequential, and differentiated instruction has not been systematically designed. Teachers’ reflective practices also tend to occur in the form of spontaneous reflection-in-action rather than structured reflection-on-action. This study constructs the concept of “situational reflective professionalism” as a form of teacher professionalism that develops through pedagogical adaptability, contextual reflection, and responsive decision-making within dynamic learning situations. Theoretically, this study contributes to the development of vocational teacher professionalism studies grounded in reflective practice and contextual learning, while practically emphasizing the importance of reflective culture, differentiated instruction, and strengthening teachers’ adaptive capacities in transforming twenty-first century vocational education.